Examples of adapted ethnographic approaches for participatory design - Kingery-Page, Katie; Glastetter, Abigail; DeOrsey, Danielle; Falcone, Jessica M. (Council of Educators in Landscape Architecture., 2017)
In landscape architecture practice, participatory design approaches emphasize community workshops and charrettes. But marginalized voices are often suppressed during group meetings, if those at the margins are invited at all. To expand inclusion in the design process, we propose adapting classic ethnographic methods such as one-on-one interviews and direct observation. The benefit of adapted ethnography is that it gives us first-person accounts of a place and of people’s needs. Adapted ethnographic methods allow designers to observe how people really use and feel about places, and are well-suited to one-on-one interactions with stakeholders. Although ethnographic methods can be usefully adapted to landscape architecture processes, this adaptation differs from true ethnography. Developing an ethnographic narrative is a deep and long term endeavor, often occupying the majority of an ethnographer’s career. To adapt ethnographic methods for use during a relatively short period of time, a spatial designer must limit the inquiry to a specific “lens” or particular question related to the community design at hand. Recently, we used an adapted ethnographic approach in the design process for a temporary park and associated streetscape in a Midwestern city with slightly less than a half million residents. We sought to understand downtown resident’s lived experiences downtown, their perceptions of downtown place identity, and what they most valued in a temporary park.
Citation: Kingery-Page, K., Glastetter, A., DeOrsey, D., and J.Falcone (2016)."Examples of adapted ethnographic approaches for participatory design. Landscape Research Record, 5.
Keywords: Participatory design; Adapted ethnography; Community engagement; Temporary landscape; Public space